2003
DOI: 10.1002/pmic.200300619
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of hairy root from Panax ginseng C. A. Meyer using peptide fingerprinting, internal sequencing and expressed sequence tag data

Abstract: As an initial step to the comprehensive proteomic analysis of Panax ginseng C. A. Meyer, protein mixtures extracted from the cultured hairy root of Panax ginseng were separated by two-dimensional polyacrylamide gel electrophoresis (2-DE). The protein spots were analyzed and identified by peptide finger printing and internal amino acid sequencing by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) and electrospray ionization quadrupole-time of flight mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 22 publications
2
36
2
Order By: Relevance
“…In this sense, a common approach for protein extraction has been to homogenize the plant material in the presence of liquid nitrogen, precipitate the protein content in a trichloroacetic acid/acetone solution and re-solubilize the pellet in a chaotropic agent [18]. Due to its simplicity, it remains the preferred protocol of total protein extraction from root tissue, as demonstrated by recent proteomic studies of wheat [19], maize [20], Medicago trunculata [21], rice [22] and ginseng [23] roots.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In this sense, a common approach for protein extraction has been to homogenize the plant material in the presence of liquid nitrogen, precipitate the protein content in a trichloroacetic acid/acetone solution and re-solubilize the pellet in a chaotropic agent [18]. Due to its simplicity, it remains the preferred protocol of total protein extraction from root tissue, as demonstrated by recent proteomic studies of wheat [19], maize [20], Medicago trunculata [21], rice [22] and ginseng [23] roots.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Dried samples were resolved in four different lysis buffers, respectively [16][17][18][19][20]. The common components they contained were 2 % CHAPS, 1 % PMSF, and 1 % protease inhibitor; and the differences were lysis buffers I: 8 M urea; Lysis buffers II: 7 M urea, 2 M thiourea; Lysis buffers III: 6 M urea, 2 M thiourea; Lysis buffers IV: 5 M urea, 2 M thiourea.…”
Section: Protein Extractionmentioning
confidence: 99%
“…Although more than 80 different skeletal types of triterpenes are known to occur naturally, the dammarane-type triterpenes are found only in a few species as major compounds, e.g., P. ginseng [2] and Gynostemma pentaphyllum (jiaogulan) [3]. Recent research including large-scale gene analysis [4][5] and proteome analysis [6][7] has shown that P. ginseng is one of the most suitable systems for studying the biosynthesis of dammarane-type triterpene saponins. The isoprenoid biosynthetic pathway plays an important role in plant metabolism.…”
Section: Introductionmentioning
confidence: 99%